FAKTOR-FAKTOR YANG MEMPENGARUHI DIVERSIFIKASI PENDAPATAN PETANI KUBIS - Tambunan, Herlina Yolanda; Sitohang, Maryanti; Sibotolungun Sipahutar, Bahagia (Universitas Katolik Santo Thomas Medan, 2025)
This study aims to: (1) determine the income of cabbage farmers in Lobu Tolong Village, Peranginan District, Humbang Hasundutan Regency, North Sumatra; (2) measure the level of diversification of farmers' income; and (3) analyse the factors that influence the diversification. The sampling method used Simple Random Sampling. Data were analysed using income analysis, diversification index (HHI and SID), and multiple linear regression. The results showed that the average income of cabbage farmers was IDR 2,115,308.33 per growing season. The Herfindahl Index (HHI) value is 0.74117 and the Simpson diversification index (SID) is 0.25883, which indicates that the level of income diversification is in the medium category. Statistically (simultaneously and partially), the factors of age, education, number of family members, and land area have no significant effect on the level of income diversification of farmers.